(untitled) (Orfeu, 2018)
With the objective of analyzing the presence or absence of Music Performance Anxiety (MPA) in consolidated instrumental duos, six semi-structured interviews with members of three long-term instrumental chamber music duos (violin and piano; cello and piano; piano 4-hands duo) were conducted. The analysis showed that MPA is somewhat common to all the musicians, but that the “duo” was considered to be a safe place or place of refuge as compared to that of solo performance. The causes of MPA in duo performance for those interviewed were related to family and to the environment in which they were raised. In addition, a reluctance to speak about MPA between the duo members prevailed. The lack of an educational system to promote knowledge and to assist in the development of coping strategies was noted. Differing attitudes were observed across the generational gaps of the duos with regard to solving the problem of MPA. However, all agreed that a positive psychosomatic attitude and healthy lifestyle, coupled with the application of breathing techniques and concentration, are effective means to countering the problems of MPA. Regarding their perceptions of performing with the regular partner in a long-term or consolidated duo as opposed to an occasional partner in a short-term duo, all interviewees affirmed the preferred satisfaction that the long-term commitment gave, noting that it provided “another perception, another poetry”.